2010
DOI: 10.1007/s00436-010-1910-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of plant extracts on human Loa loa isolates and cytotoxicity for eukaryotic cells

Abstract: Loa loa, a filarial worm, can cause fatal encephalitis in humans. In an attempt to find alternatives to the standard treatments (ivermectin and diethylcarbamazine citrate), we tested 12 methanolic extracts of nine traditional plant remedies. The extracts (100-0.09 microg/ml) were incubated with 20 Loa loa microfilariae isolated from patients at 37 degrees C with 5% CO(2) in modified Eagle's medium supplemented with 10% fetal serum and antibiotics. Activity was evaluated 120 h later by counting live microfilari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 17 publications
2
14
0
2
Order By: Relevance
“…In the MTT test, HypoE22 cells were stimulated with the extracts in the range 0.1-10 μg/mL and a null effect on cell viability was observed (Figure 2). This is consistent, at least in part, with previous studies suggesting anti-proliferative effects induced by P. africanum extracts at higher concentrations [37,38]. Based on results gathered from the MTT test, a concentration of 10 μg/mL was chosen for evaluating protective and neuromodulatory effects.…”
Section: Resultssupporting
confidence: 77%
“…In the MTT test, HypoE22 cells were stimulated with the extracts in the range 0.1-10 μg/mL and a null effect on cell viability was observed (Figure 2). This is consistent, at least in part, with previous studies suggesting anti-proliferative effects induced by P. africanum extracts at higher concentrations [37,38]. Based on results gathered from the MTT test, a concentration of 10 μg/mL was chosen for evaluating protective and neuromodulatory effects.…”
Section: Resultssupporting
confidence: 77%
“…The plant grows in tropical Africa, from Senegal to southern Chad and Central African Republic and from Gabon to DR Congo and northern Angola. In traditional medicine, the plant is used as antiemetic, lotion for skin disorders (Mengome et al, 2010), remedy for pneumonia, cough, fever, rheumatism, vomiting, epilepsy (Kone et al, 2006) and bacterial diseases (Kone et al, 2004). The cytotoxicity of the methanol extract from fruit was reported toward CCRF-CEM cells (IC 50 : 4.23 μg/mL), CEM/ADR5000 cells (IC 50 : 4.44 μg/mL), MDA-MB-231- pcDNA cells (IC 50 : 25.85 μg/mL), MDA-MB-231- BCRP cells (IC 50 : 4.17 μg/mL), HCT116 ( p53 +/+ ) cells (IC 50 : 3,69 μg/mL), HCT116 ( p53 −/− ) cells (IC 50 : 3.09 μg/mL), U87MG cells (IC 50 : 8.01 μg/mL), U87MG.Δ EGFR cells (IC 50 : 8.68 μg/mL), and HepG2 cells (IC 50 : 19.90 μg/mL) (Kuete et al, 2015e).…”
Section: Hit Cytotoxic Plants Of Central East and West Africamentioning
confidence: 99%
“…they do not show high safety indices. An example of this toxic profile can be seen in the work of Mengome and co-workers 54 in which monkey kidney cells were used for the cytotoxicity evaluation. In this same context, another recent study showed that 3alkylpyridine marine alkaloid analogues showed significant toxicity against murine peritoneal macrophages.…”
Section: Introductionmentioning
confidence: 99%